The Effect of Shalat Movement on Cardiorespiratory Fitness in The Elderly - Munthe, Zakiyah Darajat; Boy, Elman; Furqon, Al (Universitas Muhammadiyah Semarang, 2021)
Background: An elderly is a stage of human development after adulthood and the last period of the human life cycle. As a person gets older, the disability increases in activities of daily life as a result of decreasing physical level. The aging process shows physiological, cognitive and psychological changes in the human body. Decreased components of fitness, such as muscle strength, balance and the cardiorespiratory system affect the development of disabilities. Therefore, in Islam there is prayer service, which can be an effort to improve the cardiorespiratory fitness of the elderly. Where, with prayer, it can become a sports medium that is both physical and spiritual.Objective: To determine the effect of movement on cardiorespiratory fitness in the elderly. Research method: This type of literature study is a literature review.Method: the method used in writing this article is English studies relevant to the topic was carried out using the PubMed, Google Scholar and Semantic Scholar databases, restricted from 2010 to 2020. The keywords used in the article search were elderly, prayer movement and cardiorespiratory fitness.Results: The effect of prayer movement on cardiorespiratory fitness is that it can improve blood circulation from the heart to the rest of the body, increase blood flow to the brain and increase lung elasticity.Conclusion: There is a significant effect of prayer movement on the increase in cardiorespiration of the elderly.